On the theory of groups with generalized minimality condition for closed subgroups - Charin, V. S. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We prove that a topological Abelian locally compact group with generalized minimality condition for closed subgroups is a group of one of the following types: 1) a group with minimality condition for closed subgroups, 2) an additive group of theJ p -ring of integerp-adic numbers, 3) an additive groupR p of the field ofp-adic numbers (p is a prime number).